Script and Creating a Religious Identity: The Typography of the Talmud - Ефрат Гроссман (Культура і мистецтво у сучасному світі)
Aim of the article. This article deals with the iconic typography of the Talmud page and focuses on the relationship between script and religious identity. It examines changes in design and typography in the modern editions of Steinsaltz, Artscroll, and Koren since the 1980s, and how they led to the removal of some of these editions from the yeshiva world, preventing yeshiva students from using them. Results. The Talmud is the central and most influential text in the world of Jewish law. Its study holds great spiritual significance, and many regard it as a means for self-expression and connection to the Torah’s oral tradition. During the second half of the 20th century, initiatives were taken to change the traditional layout of Judaic texts. The aim of these initiatives was to create a new “Israeli design” for Judaic texts while remaining loyal to the past. Designers sought to strike a balance between conservation and innovation in aspects such as book design, technological advances in the printing industry, accessibility regarding reading, studying, and prayer, and catering to broader target audiences. In most cases, new book formats were chosen, but at times, such changes generated strong opposition in certain Jewish sectors, resulting in those books being banned from study halls and synagogues. A case in point was Rabbi Steinsaltz’s project of redesigning the Talmud to make Talmud study more accessible for struggling learners. Rabbi Steinsaltz changed the format of the Talmud page to a more readable format, using new fonts, additional punctuation, and wider spacing between the lines. This change, however, was not accepted by the Haredi (ultra-Orthodox) and parts of the National- Religious public. Scientific novelty. Existing research deals separately with the issue of Zionist Hebrew typography and the issue of the ultra-Orthodox society. To the best of our knowledge, so far, no research has directly linked the two issues to examine the ultra-Orthodox approach to design in general and to Hebrew typography in particular. This study contributes to previous research on Hebrew typography, emphasising its role in conveying a social, educational, and ideological message, regardless of the written text’s content. Conclusions. Judaic texts that are used in the ultra-Orthodox world are visually different in design from those used in the secular and/ or National-Religious world. While the ultra-Orthodox staunchly preserve the traditional Judaic book format (albeit with minor changes), the secular world and parts of the National-Religious public welcome books that have a variety of fonts, colorful designs and pictures, decorations, and didactic explanations to aid the reader. The Talmud is a book with a distinct typography and contains a wealth of information. The layout of a Talmud page allowed for a variety of different texts to be combined in one book, making it easier to study. The fixed template, which is exactly the same in all tractates, generates a visual representation of the text so that a large amount of information can be remembered through an “eidetic memory” of images. Rabbi Adin Steinsaltz’s edition of the Talmud (Koren), which changed the traditional page layout to make the text more accessible, remained only partially faithful to the original but brought about a true revolution. For some audiences, this innovative edition represents a pinnacle of Hebrew literature, while for others, it is seen as a violation of the sacred literature and should be banned. There has always been a strong connection between the ultra-Orthodox world and Hebrew typography, and it is still present on a daily basis. The Hebrew letters are cornerstones in the design of the Holy Scriptures. However, the attitude of the ultra-Orthodox world toward modern Hebrew typography as reflected in this study, is one of ambivalence, some acceptance but mostly strong reservations.